Ruang Kreativitas Dalam Masyarakat Modern Berbasis Solidaritas - Yensi Purwanti; Sindi Ariska Dwi Agustin; Tarish Auliasari Narulita (Jurnal Riset Sosial Humaniora dan Pendidikan, 2023)
The existence of Community Learning Activity Centers (PKBM) aims to form managed learning media that is centered on empowering local potential in increasing the knowledge, skills and attitudes of the community in the economic, social and cultural fields. In developing a community, community participation must be actively linked and participate in processes and activities that exist in society in order to create maximum goals. The feeling of sharing between individuals in social groups will form social solidarity so that a sense of solidarity arises between these individuals. In this study using descriptive qualitative research methods using an ethnographic approach, this study aims to find out how forms of solidarity arise between individuals in creating a community. This research is located in Gesang Village, Tempeh District, Lumajang Regency. The informant himself is the founder, administrator and member of Omah Sinau Gesang. Researchers only took 6 people to be used as informants. The informants that the researchers took consisted of one founder, one administrator, and 4 members from Omah Sinau Gesang. Data collection was obtained from the results of interviews and observations which were included with the documentation. The results of this study indicate that within a community there is a division of labor as a cause for the emergence of organic solidarity. This interdependence increases with the division of labor and with increasing specialization and differences among individuals in the community.